2011
DOI: 10.1136/jcp.2010.087999
|View full text |Cite
|
Sign up to set email alerts
|

The biology of micrometastases from uveal melanoma

Abstract: The most likely explanation for latency in this setting is the inability of uveal melanoma cells in metastatic sites to grow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
23
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 43 publications
5
23
0
2
Order By: Relevance
“…Stage 1 and stage 2 metastases may be inconspicuous on hematoxylin-eosin stains and may become apparent with immunohisto-chemical staining for HMB45. Both the previous study 12 and the present study showed a conspicuous absence of inflammatory cells in the liver associated with the melanoma metastases. Although the present study could not evaluate individual metastatic melanoma cell survival in the liver, the previous autopsy study 12 and experimental models indicate that few melanoma cells can survive in the liver for prolonged periods to spawn metastases.…”
Section: Commentsupporting
confidence: 78%
See 4 more Smart Citations
“…Stage 1 and stage 2 metastases may be inconspicuous on hematoxylin-eosin stains and may become apparent with immunohisto-chemical staining for HMB45. Both the previous study 12 and the present study showed a conspicuous absence of inflammatory cells in the liver associated with the melanoma metastases. Although the present study could not evaluate individual metastatic melanoma cell survival in the liver, the previous autopsy study 12 and experimental models indicate that few melanoma cells can survive in the liver for prolonged periods to spawn metastases.…”
Section: Commentsupporting
confidence: 78%
“…There are similarities and differences between the present study and the only previous study 12 of the his tological features of metastatic uveal melanoma to the liver. The prior study 12 found a collection of 1 to 3 melanoma cells in the liver in 1 of 6 patients with uveal melanoma who died of nonmelanoma causes.…”
Section: Commentsupporting
confidence: 46%
See 3 more Smart Citations